Satanism and paranormal events in the Diario Extra, during the 1990s. Samples of sensationalism and neoconservative optics in the Costa Rican written press - Marchena Sanabria, Jorge (2020)
This article analyzes the notes on Satanism and other paranormal events, as witchcraft and aliens, published by the Costa Rican newspaper, Diario Extra, in the last decade of the 20th century. Historically, the devil was used as a way of terrorizing society and above all, to reaffirm the submission of youth and popular classes to political-economic elites. In this case, immersed with sensationalist journalism to exacerbate panic and distract civil society, above all, in a moment of deep social tensions. Methodologically, a simplified form of discourse analysis was used, based on the proposals of theorists such as Jäger and Keller.